1999
DOI: 10.1002/(sici)1096-8628(19990319)83:3<164::aid-ajmg5>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Synteny-defined candidate genes for congenital and idiopathic scoliosis

Abstract: Idiopathic scoliosis (IS) is a common but poorly understood syndrome. Congenital scoliosis (CS) is less common but comparably unexplored. Previous studies suggest that each has a significant genetic component. However, the occurrence of scoliosis in the presence of other hereditary connective tissue syndromes raises the possibility that IS and CS are in fact a heterogeneous group of disorders with varied pathogenetic mechanisms. Mouse mutations have proven informative in identifying genes that are important in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 154 publications
0
14
0
Order By: Relevance
“…The pudgy mouse phenotype, which is similarly characterized by severe vertebral and rib defects, 18 has been shown to be due to mutations in DLL3 19,20 . Synteny conversion indicated that the human orthologue for DLL3 localized to 19q13.1 21 . Turnpenny and colleagues subsequently identified mutations in DLL3.…”
Section: Vertebral Malformation Syndromes With Known Genetic Etiologymentioning
confidence: 99%
“…The pudgy mouse phenotype, which is similarly characterized by severe vertebral and rib defects, 18 has been shown to be due to mutations in DLL3 19,20 . Synteny conversion indicated that the human orthologue for DLL3 localized to 19q13.1 21 . Turnpenny and colleagues subsequently identified mutations in DLL3.…”
Section: Vertebral Malformation Syndromes With Known Genetic Etiologymentioning
confidence: 99%
“…Therefore, these 20 genes including basic transcription factor 3-like 4 ( Btf3l4 ) and epidermal growth factor receptor pathway substrate 15 ( Eps15 ) are potential candidate genes. Furthermore, the mapping results exclude 2 strong candidate genes, collagen, type IX, alpha 2 ( Col9A2 ) and sex comb on midleg homolog 1 ( Scmh1 ), both located on chromosome 4, distal to the b gene [9, 26]. A mutation in the human homolog of the Col9A2 gene causes multiple epiphyseal dysplasia type 2 [20] resulting in hypoplasia of anterior vertebral elements [2].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore undertook a systematic review of mouse mutations with skeletal, tail, or neuromuscular phenotypes with the goal of identifying potential human candidate genes for CS and IS. 74 When the human homologue of the mouse mutant gene was known, this became a candidate. When such a homologue was not known, the established syntenic relationships between the two species were used to identify additional human candidate genes by their chromosomal locations.…”
Section: Use Of Synteny Analysis To Identify Candidate Genes For Humamentioning
confidence: 99%